2020
DOI: 10.1177/1049732320978202
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Recovery Through Resilience: Insights From Adults in Midlife Living With Anorexia Nervosa

Abstract: Despite the high percentage of adults living with anorexia nervosa (AN) over the life course, there is limited understanding of what it means to be living with AN in midlife when the majority of research has focused on adolescents and young adults. As such, clinical practice for individuals in midlife is informed by a severe and enduring AN (SE-AN) framework, which assumes that recovery is not necessarily feasible past young adulthood. This study used constructivist grounded theory methodology to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
(83 reference statements)
0
9
0
3
Order By: Relevance
“…There were 13 papers with a treatment experience focus, half of which [ 45 , 51 , 68 , 69 , 72 , 74 ] reported on novel, non-evidence-based interventions. Relatively fewer papers cited participant experiences of temporal processes of change and recovery, whereby only four of the 36 (8.6%), had the specific focus of recovery [ 46 , 58 , 61 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 papers with a treatment experience focus, half of which [ 45 , 51 , 68 , 69 , 72 , 74 ] reported on novel, non-evidence-based interventions. Relatively fewer papers cited participant experiences of temporal processes of change and recovery, whereby only four of the 36 (8.6%), had the specific focus of recovery [ 46 , 58 , 61 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…All the participants experienced shame and the desire to "clean" their "gross" bodies, as they somehow felt responsible for the abuse. This "shame" was further compounded by the stigma associated with living with an eating disorder (Firkins et al, 2019;McCallum & Alaggia, 2021). This participant, in particular, wanted to remove the shame, layer by layer.…”
Section: Again I Am Above the Sea But This Time I Will Follow Those Beaconsmentioning
confidence: 99%
“…While experiences of stigmatization and feelings of self-stigmatization due to low social position and failure to comply with a healthy lifestyle were widespread among the participants, they were most profound among the midlife participants (Rasmussen, Petersen, et al, 2021). A qualitative study by McCallum and Alaggia (2020) similarly showed that patients who suffered from an eating disorder felt that they carried a double stigma: stigma associated with their illness and stigma of being at midlife while suffering from their illness. The findings of this PhD study illustrate a triple stigma among midlife socially disadvantaged ischemic heart patients: stigma associated with an illness that is considered caused by the patients' lifestyle, stigma associated with developing the illness early, and stigma associated with being socially disadvantaged.…”
Section: Problematic Healthcare Interactions and Stigmatizationmentioning
confidence: 99%
“…Recent empirical qualitative studies have indicated that living with a chronic illness at midlife may also create distinct and particularly burdening psychosocial challenges (Markle et al, 2015;Martinsen et al, 2015;McCallum & Alaggia, 2020). Markle, Attell, and Treiber (2015) showed how midlife patients living with multiple chronic illnesses experienced psychosocial challenges, such as inconsistency between the illness identity and their self-image, concerns about the future, loss of job identity, and stigmatization related to their illness, all of which created social isolation.…”
Section: Midlife Patientsmentioning
confidence: 99%
See 1 more Smart Citation